The effect of shuttle run training on badminton footwork agility in athletes - Muhammad Rinto Prasetyo; Syamsuramel Syamsuramel; Silvi Aryanti (Sriwijaya Journal of Sport, 2025)
Research Problems: Agility is a crucial factor in athlete performance to improve mobility and response on the field. Research Objectives: The purpose of this study was to determine the effect of shuttle run training on the results of footwork agility in badminton athletes BC. Pusri Palembang. Methods: The research method used is quantitative with a pretest and post-test one group research design. The population in this study were male athletes aged 10-15 years old club which amounted to 30 people. The sample used was 30 people with total sampling technique. This research instrument is the shuttle run test. In this study, the treatment applied was training given for six weeks. Results: The results of the hypothesis test show that the tcount is 5.516> ttable 2.045. Thus, it can be concluded that Ho is rejected, and Ha is accepted. Conclusion: Based on the test, the shuttle run exercise is stated to the athlete's footwork agility. The findings found that shuttle run training is one of the effective methods to improve footwork agility in badminton.